2021
DOI: 10.3390/ijms22126521
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Affecting Thyroid-Stimulating Hormone and Thyroid Hormone Levels

Abstract: Thyroid hormones are necessary for the normal functioning of physiological systems. Therefore, knowledge of any factor (whether genetic, environmental or intrinsic) that alters the levels of thyroid-stimulating hormone (TSH) and thyroid hormones is crucial. Genetic factors contribute up to 65% of interindividual variations in TSH and thyroid hormone levels, but many environmental factors can also affect thyroid function. This review discusses studies that have analyzed the impact of environmental factors on TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 465 publications
(542 reference statements)
0
49
1
3
Order By: Relevance
“…It is known that many environmental factors and disruptors as well neuropeptides affect the production and secretion of TSH ( 3 , 4 ). In our previous study, we proved a positive correlation between ghrelin and TSH concentrations in children with ISS.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that many environmental factors and disruptors as well neuropeptides affect the production and secretion of TSH ( 3 , 4 ). In our previous study, we proved a positive correlation between ghrelin and TSH concentrations in children with ISS.…”
Section: Introductionmentioning
confidence: 99%
“…We also observed decreased levels of FT3, FT4 and TSH after two months of physical activity. This finding was not surprising if we considered that exercise has an effect on body homeostasis (i.e., skeletal muscles and cardiac activity) involving the hypothalamus-hypophysis-thyroid axis [60]. Indeed, thyroid hormones and TSH levels changes are expected after physical exercise.…”
Section: Discussionmentioning
confidence: 92%
“…A large population study by Song et al, involving 10,566 participants showed an increase in calcitonin levels in male smokers [ 17 ]. Smoking affects the normal functioning of the thyroid gland [ 39 ]; however, the effect of smoking on calcitonin-producing C cells has not been elucidated [ 17 ]. The results of Tabassian et al suggested that the lungs are the source of increased calcitonin in smokers rather than the thyroid.…”
Section: Environmental Factors That Affect Pth and Calcitonin Levelsmentioning
confidence: 99%